Digital terrain and automated mapping system development using unified modelling language (UML) - Abdul Rahman, Alias; Jae, Hong Yom (2004)
Automated mapping and digital terrain system could be developed by using several approaches where an object oriented technique is one of them. The technique has been considered by many software engineers and developers as one of the most efficient approaches. This paper discusses the design and development of digital terrain and automated mapping system using the Unified Modelling Language (UML). The design and the development aspects will be highlighted and forms major discussion of the paper. The digital terrain modeling component is based on Triangular Irregular Network (TIN) data structure. We will demonstrate the system by using photogrammetrically captured data. The application of the system will be demonstrated and finally we will highlight the system's outlook.